Mobile Web - Tosete, Francisco (Anuario ThinkEPI, 2008)
In the past year and a half, we have seen a forceful consolidation of what is called the Mobile Web. Parallel to its development, an ample number of devices (mobile telephones, PDAs, UMPCs, SmartPhones, etc) have appeared that allow users to interconnect and also access the Internet fromany place with a wireless connection. Mobility, and especially geopositioning, opens up new services and possibilities in leisure, culture, business, and work patterns. We are witnessing the beginnings of the Mobile Web, another whole new revolution for our paper world. If Gutenberg were alive, he would really be surprised.